PEUBAH LAJU TUMBUH RELATIF DAN PROTEIN BERPERAN PENTING DALAM MENINGKATKAN KUALITAS BENIH KEDELAI (Glycine max L. Merr) - Rudi Hartawan (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
Variables of seed quality are correlated each others, especially in storage. This fact needs investigation to predict main variables for measuring seed quality at storage. The objectives of this study were to investigate the main variables on growth analysis and seed quality using path analysis in production of extension seed. The field trial was carried out at Sebapo Experimental Station, Jambi and laboratory works were conducted in the Center for Post Harvest Research and Development, The Ministry of Agriculture and Center for Forest Research and Development, The Ministry of Forestry, Bogor from April until December 2010. The experimental design used was an unformatted design. The research showed that relative growth rate and protein were the main variables to improve soybean seed quality.